2002
DOI: 10.1021/cm011656+
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Various Methods for the Preparation of Polystyrene and Poly(methyl methacrylate) Clay Nanocomposites

Abstract: Polymer-clay nanocomposites of styrene and methyl methacrylate have been prepared by bulk, solution, suspension, and emulsion polymerization as well as by melt blending. Two different organic modifications of montmorillonite have been used: one contains a styryl monomer on the ammonium ion while the other has no double bond. The organic modification as well as the mode of preparation determines if the material will be exfoliated or intercalated. Exfoliation is more likely to occur if the ammonium ion contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
199
4
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(221 citation statements)
references
References 19 publications
15
199
4
3
Order By: Relevance
“…All the examined bodies had the hierarchical microrelief available for the morphological characterization, wherein this microrelief was similar to that presented in the publications on polystyrene (e.g., in [21][22][23]) and other polymers (e.g., [24][25][26]). …”
Section: Morphological Memory Of the Polystyrene Bodiessupporting
confidence: 64%
“…All the examined bodies had the hierarchical microrelief available for the morphological characterization, wherein this microrelief was similar to that presented in the publications on polystyrene (e.g., in [21][22][23]) and other polymers (e.g., [24][25][26]). …”
Section: Morphological Memory Of the Polystyrene Bodiessupporting
confidence: 64%
“…In situ polymerization is a challenging one, as it allows us to adjust the chemistry to optimize the affinity between filler and the resulting polymer. Different types of polymerization methods have been used to prepare polymer nanocomposites, such as solution, suspension or emulsion, and free radical polymerizations (Akelah & Moet, 1996;Wang et al, 2002;Chen et al, 2000;Zhou et al, 2001). This variety to prepare polymer nanocomposites by in situ polymerization was mostly explored with clays.…”
Section: Preparation Of Nanocompositesmentioning
confidence: 99%
“…The various LDH additives all increase the molecular weight of the PMMA composites compared to that prepared in the absence of an LDH; CaAl gives the highest Mw, about twice that in the absence of an LDH, but MgAl and NiAl are only a little larger than pristine PMMA. These results should be compared to reported data where the influence of additive type on PMMA prepared by bulk polymerization was observed: the molecular weight of PMMA extracted from PMMA VB-16 (VB-16 is an organically modified MMT, a cationic clay) was almost double the molecular weight of pristine PMMA and PMMACloisite 10A prepared by bulk polymerization under similar conditions [4]. Wang et al, on the other hand, reported a slight decrease in both the weight average molecular weight (Mw), the number average molecular weight (Mn) and an increase in the polydispersity index of the disordered-exfoliated PMMA-undecenoate LDH nanocomposites prepared by bulk polymerization [17].…”
Section: Molecular Weight Of Solvent Extractable Polymer-ldh Nanocompmentioning
confidence: 60%
“…Clay/polymer nanocomposites often have properties that are dramatically different from those of the polymer alone with unique improvements in mechanical strength [4], thermal stability [5], flammability [6] and gas permeability [7]. The compatibility of the clay between the polymer and the clay is crucial for the formation of well-dispersed nanocomposites [6].…”
Section: Introductionmentioning
confidence: 99%